The Child Marriage Trends in 3T Regions of Sumatra: The Impact of Law No. 16/2019 and the Covid-19 Pandemic on Poor Communities - Wahyuni, Budi; Nur, Ratih Hidayah; Purwatiningsih, Sri (Populasi, 2024)
The study "Identification of Changes in Marriage Trends Age < 19 years Post the Law No. 16/ 2019 and in Covid Age 19 in Rural and Urban Poor, in 3T (Outer, Remote, and Frontier) Region of Sumatra Island" was carried out by PERMAMPU (Perempuan Sumatra Mampu) in 26 villages distributed over 26 districts, in 8 provinces on the island of Sumatra, using the FPAR (Feminist Participatory Action Research) method. This study is undermined by PERMAMPU's concerns about the increasing data and practice of child marriage and early marriage <19 years especially in the countryside, although the Marriage Law No. 1 of 1974, which previously allowed 16 years of marriage for women and 19 years for men, has been reduced to a minimum age of 19 years in women and men through the Law No.1 of 2019. The FPAR method focuses on the life stories of women and related stakeholders. The information and data obtained from 1,147 sources (986 women & 161 men) resulted in 32 case studies. In addition to qualitative data, also obtained quantitative data that showed an increasing trend in child-age marriage practices. This is typically caused by, among other things, a lack of understanding of Law No. 16 of 2019 and a low level of education about sexual and reproductive health rights, which led to unwanted pregnancies, school dropouts, and poverty.